From a lost world: an integrative phylogenetic analysis of Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae), with the description of a new species - Waser, Lea E.; Schweizer, Manuel; Alexander, Haas; Das, I.; Jankowski, André; Pui, Yong Min; Hertwig, S.T. (Springer Verlag, 2017)
While the island of Borneo is considered a global biodiversity hotspot, the species richness in many groups remains unknown and appears underestimated. During herpetological surveys carried out in the interior of Sarawak, East Malaysia, several individuals of a small species of the genus Ansonia Stoliczka 1870 were collected on the Usun Apau plateau and in the Gunung Hose mountain range (Ansonia sp. Usun Apau). An integrative taxonomic approach comprising phylogenetic (2.4 kb mitochondrial rDNA fragment, Bayesian Inference and Maximum Likelihood, >5.1 % to its closest relative) and morphometric analyses (25 measurements, multivariate ratio analysis and linear discriminant analysis), as well as morphological comparisons support the status of this operational taxonomic unit as a separate taxon at species level. The obtained phylogenetic hypothesis corroborates the two major clades within Ansonia found in previous studies. Within Clade One Ansonia sp. Usun Apau and the enigmatic Ansonia torrentis are part of a monophyletic group of the Bornean species Ansonia hanitschi, Ansonia minuta, Ansonia platysoma, Ansonia spinulifer, Ansonia vidua, and two additional undescribed taxa. This subclade must be considered as the result of an on-island radiation in the complex evolution of Ansonia. The new species is formally described including the identification of diagnostic morphometric traits. Ansonia sp. Usun Apau is endemic to two isolated mountain ridges in central Sarawak and must be considered as a new element of the unique diversity of the Bornean amphibian fauna that is potentially threatened by habitat loss at least in parts of its range.